The Genesis of Cerebellar GABAergic Neurons: Fate Potential and Specification Mechanisms - Leto, Ketty; Rolando, Chiara; Rossi, Ferdinando (Frontiers in Neuroanatomy, 2012)
All cerebellar neurons derive from progenitors that proliferate in two germinal neuroepithelia: the ventricular zone (VZ) generates GABAergic neurons, whereas the rhombic lip is the origin of glutamatergic types. Among VZ-derivatives, GABAergic projection neurons, and interneurons are generated according to distinct strategies. Projection neurons (Purkinje cells and nucleo-olivary neurons) are produced at the onset of cerebellar neurogenesis by discrete progenitor pools located in distinct VZ microdomains. These cells are specified within the VZ and acquire mature phenotypes according to cell-autonomous developmental programs. On the other hand, the different categories of inhibitory interneurons derive from a single population of Pax-2-positive precursors that delaminate into the prospective white matter (PWM), where they continue to divide up to postnatal development. Heterotopic/heterochronic transplantation experiments indicate that interneuron progenitors maintain full developmental potentialities up to the end of cerebellar development and acquire mature phenotypes under the influence of environmental cues present in the PWM. Furthermore, the final fate choice occurs in postmitotic cells, rather than dividing progenitors. Extracerebellar cells grafted to the prospective cerebellar white matter are not responsive to local neurogenic cues and fail to adopt clear cerebellar identities. Conversely, cerebellar cells grafted to extracerebellar regions retain typical phenotypes of cerebellar GABAergic interneurons, but acquire type-specific traits under the influence of local cues. These findings indicate that interneuron progenitors are multipotent and sensitive to spatio-temporally patterned environmental signals that regulate the genesis of different categories of interneurons, in precise quantities and at defined times and places.